2004
DOI: 10.1007/s00122-004-1793-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and isolation of the F/f gene for femaleness in cucumber (Cucumis sativus L.)

Abstract: The biological processes leading to sex expression in plants are of tremendous practical significance for fruit production of many agricultural and horticultural crops. Sex-expression studies in cucumber showed that the different sex types are determined by three major genes: M/m, F/f and A/a. The M/m gene in the dominant condition suppresses stamina development and thus leads to female flowers. The F/f gene in the dominant condition shifts the monoecious sex pattern downwards and promotes femaleness by causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
95
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 28 publications
6
95
0
Order By: Relevance
“…Gynoecious lines of cucumber produce more ethylene than monoecious or andromonoecious ones (Owens et al 1980;Yamasaki et al 2001), and have an additional gene for ACS1 (1-aminocyclopropane-1-carboxylate synthase 1) (Trebitsh et al 1997;Mibus and Tatlioglu 2004;Knopf and Trebitsh 2006). Recently, it has also been reported that the andromonoecious sex-phenotype of cucumber and melon is the result of a reduction in ethylene production conferred by a mutation in an ACC-synthase gene (Boualem et al 2008(Boualem et al , 2009Li et al 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Gynoecious lines of cucumber produce more ethylene than monoecious or andromonoecious ones (Owens et al 1980;Yamasaki et al 2001), and have an additional gene for ACS1 (1-aminocyclopropane-1-carboxylate synthase 1) (Trebitsh et al 1997;Mibus and Tatlioglu 2004;Knopf and Trebitsh 2006). Recently, it has also been reported that the andromonoecious sex-phenotype of cucumber and melon is the result of a reduction in ethylene production conferred by a mutation in an ACC-synthase gene (Boualem et al 2008(Boualem et al , 2009Li et al 2009).…”
Section: Introductionmentioning
confidence: 94%
“…Yin and Quinn (1995) proposed that ethylene played a crucial role in regulating the sex expression in cucumber, while Kater et al (2001) proposed that the sex determination is restricted to particular whorls, rather than to their sexual identity. Recent studies cloned the F-locus in gynoecious lines as an additional copy of the ACC synthase (ACS) gene, which further conWrmed the role of ethylene in the promotion of female cucumber Xowers (Trebitsh et al 1997;Mibus and Tatlioglu 2004;Knopf and Trebitsh 2006). Kahana et al (1999) and Yamasaki et al (2003), respectively, examined the expression patterns of genes responsible for ethylene production and reception.…”
Section: Introductionmentioning
confidence: 97%
“…Sex determination follows selective arrest of development of either the staminate or the pistillate primordia (Bai et al, 2004). Cucumber sex expression is mainly determined by the genes F, m, a, gy, and h. The Female (F ) gene regulates the number of female flowers and was cloned and shown to encode 1-aminocyclopropane-1-carboxylic acid synthase (CsACS1G), which is involved in ethylene biosynthesis (Trebitsh et al, 1997;Mibus et al, 2004). The andromonoecious gene (M ) was also identified as a previously characterized putative 1-aminocyclopropane-1-carboxylic acid syn-thase gene CsACS2, while the m allele is mutated at a conserved site (Gly33Cys).…”
Section: Introductionmentioning
confidence: 99%